An approach for the pore-centred description of adsorption in hierarchical porous materials. Issue 41 (19th August 2022) - Evans, Jack D.
Abstract : Analysis of metal–organic frameworks featuring hierarchical pore systems is presented and leveraged to understand adsorption in unique pore structures. Abstract : Analysis of pore size distributions based on crystalline representations of metal–organic frameworks (MOFs) featuring hierarchical pore systems, DUT-32, DUT-75, UMCM-1 and NU-1000, is presented here and leveraged to understand gas adsorption in these unique pore structures. Statistical analysis was used to effectively partition the pore space into distinct regions labelled by the pore size. This pore description was used to discover how adsorbates are located, with respect to the different pores, during simulations of argon adsorption at 87 K. To further examine adsorption behaviour, a method of clustering the pore environments to locate the centre of the pore was developed. These pore centres were employed to observe the distribution of gas within the pore, describing adsorbate positions during filling events from the unique perspective of the pore centre. The methods presented here provide unsurpassed information about pore structure and adsorption properties that cannot be obtained with currently available methods and are now ready to apply to new materials to uncover new adsorption processes.